2005
DOI: 10.1007/s11085-005-8533-5
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Corrosion of Chromium–Manganese Steels in Sulfur Dioxide

Abstract: This work was aimed at explaining the corrosion mechanism of commercial Cr-Mn steels at 1073, 1173 and 1273 K in the atmospheres containing oxygen and sulfur. Three steels were selected for the investigations, two singlephase austenitic steels (Cr17Mn17 and Cr13Mn19SiCa) and a two-phase austenitic-ferritic steel Cr15Mn19. On all studied steels triplex scales were formed. The inner very thin, fine-grained part of the scale contained manganese, chromium and iron sulfides and oxides, the intermediate layer was bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Comprehensive studies on the scale formation mechanism of an outer mixed oxide/sulfide layer on ferritic alloys aged in an oxidizing and sulfidizing atmosphere were previously presented in various publications . Previously published work mainly proposed the aging mechanisms after long time aging experiments and did not focus on the initial reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive studies on the scale formation mechanism of an outer mixed oxide/sulfide layer on ferritic alloys aged in an oxidizing and sulfidizing atmosphere were previously presented in various publications . Previously published work mainly proposed the aging mechanisms after long time aging experiments and did not focus on the initial reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The present flue gases produced during combustion are highly reactive and contain corrosive components like carbon dioxide, oxygen, water, and sulfur dioxide. Comprehensive efforts have been made to study scale formation in ferritic‐martensitic high temperature alloys in flue gas and sulfurizing atmosphere by means of long time corrosion experiments ( t > 250 h) . The formation of an inner and outer scale in relation to the former metal surface are well known, whereby the microstructure and phase composition of the scale strongly depends on the Cr‐content of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, research in this field is very multidisciplinary, spanning a broad range from water vapour assisted corrosion processes in boiler steels [1][2][3], steam turbine blades [4][5][6] or jet propulsion engines [7,8] to extremely corrosive mixtures (SO x ; NO x ; HCl or molten salts) in waste incineration plants [4,[9][10][11]. Ferritic steels containing aluminium, chromium or silicon, especially for electric heating devices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Radiometric analysis has indicated that the inward transport of sulfur is primarily due to the SO 2 /S 2 molecular transport. Sulfides were observed in the inner scale layer [6]. However, the effect of sulfur on corrosion in an oxy-fuel system has scarcely been studied [7].…”
Section: Introductionmentioning
confidence: 99%